DETONATION PROPERTIES OF AMMONIUM NITRATE CONTAINING CALCIUM CARBONATE, DOLOMITE, AND FLY ASH - Gezerman, Ahmet Ozan; Corbacioglu, Burcu Didem (BEGELL HOUSE INC, 2017)
Because of its low cost and easy availability, ammonium nitrate (AN) is widely used in the agricultural industry; however, the explosive properties of this compound are often exploited for misuse in illegal activities. To minimize the use of AN outside the agricultural industry and to meet the nitrogen requirements of AN-based fertilizers, we attempted to use calcium carbonate, dolomite, and fly ash in different concentrations. These additives helped in reducing the explosion heat and detonation velocity of the resulting AN mixtures. According to the results of calorimetric tests, the AN mixture with a composition of 17.5% CaCO3, 7.5% dolomite, and 20% fly ash dramatically decreased the reaction enthalpy, thereby eliminating the possibility of detonation problems.
Keywords: ammonium nitrate; calcium carbonate; dolomite; fly ash; detonation; explosive heat; VELOCITY; ANFO; EXPLOSIVES; MIXTURES; ENERGY; Engineering; Materials Science